The origins and effects of macroeconomic uncertainty - Francesco Bianchi; Howard Kung; Mikhail Tirskikh (Quantitative Economics, 2023)
We estimate a production-based general equilibrium model featuring demand- and supply-side uncertainty and an endogenous term premium. Using term structure and macroeconomic data, we find sizable effects of uncertainty on risk premia and business cycle fluctuations. Both demand- and supply-side uncertainty imply large contractions in real activity and an increase in term premia, but supply-side uncertainty has larger effects on inflation and investment. We introduce a novel analytical decomposition to illustrate how multiple distinct endogenous risk wedges account for these differences. Supply and demand uncertainty are strongly correlated in the beginning of our sample, but decouple after the Great Recession.
Keywords: C11; C32; E32; G12; 330; Production-based asset pricing; uncertainty shocks; Bayesian methods; term structure of interest rates; time-varying risk premia; business cycles